2011
DOI: 10.1007/s00338-011-0853-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature stress on coral–Symbiodinium associations containing distinct symbiont types

Abstract: Several studies have demonstrated that the temperature tolerance of scleractinian reef-building corals is controlled, in part, by hosting physiologically distinct symbiotic algae. We investigated the thermal tolerance of coral-algal associations within seven common species of reef-building corals hosting distinct Symbiodinium subclades collected from Heron Island during experimentally induced bleaching conditions. During experimental heating, photosynthetic fitness was assessed by the dark-adapted yield of PSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 77 publications
12
124
0
Order By: Relevance
“…Our hypothesis was, following the OTB, that (a) antioxidant defences in Symbiodinium will increase in response to elevated temperature and declining photosynthetic performance, followed by (b) an increase in antioxidant defences of the coral host with (c) the occurrence of bleaching in the susceptible coral at high temperatures as a result of (a) and (b). For the tolerant coral M. digitata (with Symbiodinium type C15), previous work has shown that photoprotective measures might be a key element of thermal tolerance (Fisher et al, 2012), so we hypothesised that no significant antioxidant response would occur in either the symbiont or host, consistent with the OTB that identifies the symbiont as the origin of excessive ROS production under thermal stress.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Our hypothesis was, following the OTB, that (a) antioxidant defences in Symbiodinium will increase in response to elevated temperature and declining photosynthetic performance, followed by (b) an increase in antioxidant defences of the coral host with (c) the occurrence of bleaching in the susceptible coral at high temperatures as a result of (a) and (b). For the tolerant coral M. digitata (with Symbiodinium type C15), previous work has shown that photoprotective measures might be a key element of thermal tolerance (Fisher et al, 2012), so we hypothesised that no significant antioxidant response would occur in either the symbiont or host, consistent with the OTB that identifies the symbiont as the origin of excessive ROS production under thermal stress.…”
Section: Introductionmentioning
confidence: 76%
“…Data were recorded daily at noon and 30 min after sunset, with the fibre optic positioned at the same spot on the same explant at each time point. Maximum midday excitation pressure on photosystem II (Q m ), hereafter referred to as light pressure, was calculated as Q m = 1 − [(ΔF/F′ m at noon)/(F v /F m at dusk on Day 0)] (as defined by Fisher et al, 2012).…”
Section: Photobiological Variables and Sample Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the 12-months of reciprocal transplantation, MV pool corals transplanted to the HV pool showed an increase in thermal tolerance without a shift in symbiont clade . It is important to note, however, that these studies focused on clade-level differences between pools, which remains too course a resolution for studies of thermal tolerance in corals, as sub-cladal differences in thermal tolerance have been widely documented (Tchernov et al, 2004;Jones et al, 2008;Sampayo et al, 2008;Fisher et al, 2012;Hume et al, 2015).…”
Section: Symbiodinium and Host Thermal Tolerancementioning
confidence: 99%